Revisión de literatura sobre el cuadro de mando integral como herramienta de medición del desempeño organizacional (2019)
This document presents succinctly, the review of the literature related to the Balanced Scorecard - BSC, as a management tool for organizations. It also provides the reader with a starting point to know what is the BSC and its benefits, since it involves different aspects, such as a description of the components, main modifications and analysis of use cases, from the collection of published articles by different authors, in different fields of research on the BSC both in academic and productive disciplines. Likewise, the document contains the definition and generalities of other measurement tools, in order to emphasize the advantages of the implementation of the BSC, given its adaptability to any type of company, economic sector or geographical location, as supported by the analyzed cases of use, in which companies from the hotel industry, PYME, airlines, employee funds and higher education institutions, report on the benefits and impact of the implementation of the BSC in their organizations.